4 - An Explorative study of abortion among the Tarok in Central Nigeria - Titilayo Cordelia Orisaremi, (African Sociological Review, 2013)
This paper, part of a larger study, was conceived in response to the high maternal morbidity and mortality rates attributable to unsafe abortion in Nigeria. The study was predicated upon the assumption that socio-cultural practices influence the reproductive health outcome of most women in Nigeria and therefore explored these practices in relation to abortion among the Tarok ethnic group in central Nigeria. It utilized qualitative method that provided for a detailed and descriptive analysis of data from female and male respondents of various sociodemographic groups through thirty in-depth interviews and focus group discussion sessions conducted between April and May, 2008. The study found a high level of Tarok women’s exposure to unintended pregnancy, which is largely rooted in unequal gender relations, traditional gender roles and social taboos. It concludes that intervention strategies aimed at improving maternal health must go beyond the provision of, and access to contraceptives and legalisation of abortion to addressing socio-cultural practices that have overwhelming influence on the life and death of women in Nigeria.